2022
DOI: 10.1021/acs.jpca.2c00720
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Validity of Entangled Two-Photon Absorption Measurements in Organic Compounds

Abstract: Entangled two-photon absorption (ETPA) has recently become a topic of lively debate, mainly due to the apparent inconsistencies in the experimentally reported ETPA cross sections of organic molecules obtained by a number of groups. In this work, we provide a thorough experimental study of ETPA in the organic molecules Rhodamine B (RhB) and zinc tetraphenylporphirin (ZnTPP). Our contribution is 3-fold: first, we reproduce previous results from other groups; second, we on the one hand determine the effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
0
27
1
Order By: Relevance
“…It is interesting to note that as the concentration increases, the offset in CC is greater outside the dip (large delays) than inside the dip (zero delay), which is an intrinsic effect of the HOM dip as it was recently discussed. 21 This intriguing effect depicted markedly in Figure 6B, apparently implies that the HOM visibilities decrease from solvent to samples of higher concentrations, however, by using eq 8 it is found that V ref , V sol , and all V sam are essentially the same within the range of uncertainties of the experimental error, the latter determined by the noise fluctuations of the CC signal. To visualize the level of experimental uncertainties, Figure 6C presents as an example the data corresponding to the sample with the highest concentration; here the HOM sam is plotted within a known range of confidence bands, whose width represents 2 standard deviations (2σ) of the experimental data.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is interesting to note that as the concentration increases, the offset in CC is greater outside the dip (large delays) than inside the dip (zero delay), which is an intrinsic effect of the HOM dip as it was recently discussed. 21 This intriguing effect depicted markedly in Figure 6B, apparently implies that the HOM visibilities decrease from solvent to samples of higher concentrations, however, by using eq 8 it is found that V ref , V sol , and all V sam are essentially the same within the range of uncertainties of the experimental error, the latter determined by the noise fluctuations of the CC signal. To visualize the level of experimental uncertainties, Figure 6C presents as an example the data corresponding to the sample with the highest concentration; here the HOM sam is plotted within a known range of confidence bands, whose width represents 2 standard deviations (2σ) of the experimental data.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Different authors claim there is a difference up to ∼32 orders of magnitude between σ e ,, and δ c , with estimated values of σ e for molecules used as nonlinear models falling within the wide range from 10 –22 to 10 –18 [cm 2 /molecule]. ,, Although it is not completely correct to compare directly these two parameters because they have different units (σ e [cm 2 /molecule], δ c [cm 4 s/molecule]), in principle it would be possible to achieve ETPA in the low flux regime by illuminating the sample with correlated photon pairs produced by spontaneous parametric down conversion (SPDC) . Nevertheless, there is a recent debate about the actual magnitude of σ e or even if the ETPA effects has been really detected experimentally. , …”
Section: Introductionmentioning
confidence: 99%
“…Being an absorption spectroscopy method, our scheme could also be used to explore the ratio between the eTPA rate and the flux of illuminating photon pairs. With this information, one could estimate the eTPA cross section for various chemical and biological samples [35][36][37][38]. Interestingly, by exploiting additional degrees of freedom of frequency-correlated photons, namely polarization, we could explore more intriguing constructs of molecules.…”
Section: Quantum Interferometric Measurement Of Two-photon Excitation...mentioning
confidence: 99%
“…For example, two-photon absorption of time–energy entangled photons contains many nonclassical features and functionalities, including linear rather than quadratic scaling with the pump intensity, observing classically forbidden transitions, , suppressing classical one-photon resonant peaks, and manipulating excitation pathways. , A nearly 10 orders of magnitude enhancement of the two-photon absorption rate by entangled photons over classical light at the same photon fluxes has been reported, thus reducing the risk of photodamage of biological samples. However, the magnitude of this enhancement has been questioned by recent experiments and theoretical analysis. , …”
mentioning
confidence: 99%